Molecular cloning and nucleotide sequence of the type I beta-lactamase gene from Bacillus cereus. - Sloma, A (1983)
The gene for the type I beta-lactamase from Bacillus cereus has been cloned in Bacillus subtilis and Escherichia coli. In B. subtilis, penicillinase activity is detected and the enzyme is secreted. In E. coli, the gene confers ampicillin resistance. The cloned insert is 4.3 kb in length and DNA sequencing has revealed the location of the gene, its promoter and signal peptide.